The contribution of Portuguese nursing to universal health access and coverage - Ananda Maria Fernandes; Aida Maria de Oliveira Cruz Mendes; Maria Neto da Cruz Leitão; Sérgio David Lourenço Gomes; António Fernando Salgueiro Amaral; Maria da Conceição Saraiva da Silva Costa Bento (Universidade de São Paulo, 2016)
Objective: to analyze the contribution of Portuguese nursing to improving universal health access and coverage by means of the identification of nurses in the health system; evolution of health indicators; and access-promoting systems, in which nurses play a relevant role. Method: this was documentary research of publications fromnational and international organizations on planning and health outcomes. Statistical databases and legislation on health reforms were consulted. Results: nurses represent 30.18% of human resources in the national health service; the systems of access promotion performed by nurses have good levels of efficacy (95.5%) and user satisfaction (99% completely satisfied); in the local care the creation of Community Care Units (185) occurred, and 85.80% of home consultations were performed by nurses. Conclusion: political strategies, the National Health Service and strengthening of human resourcesin healthcareare the main determinants. Nursing is the most numerous professional group in the National Health Service, however numbers remaindeficient in primary health care. The improvement of academic qualification and self-regulation of this professional group has allowed for better answers inimproving health for the Portuguese.